Regional differences in productivity in Sweden: Insights from OECD regions - André, Christophe (OECD Economics Department Working Papers, 2021)
Regional inequality has increased in Sweden over the past decades, albeit from a low level. While redistribution and other public policies can narrow regional gaps in income, well-being and access to services, productivity growth is key to maintaining economic dynamism, creating job opportunities and attracting and retaining skilled workers. Against this background, this paper documents the performance of Swedish large regions (TL2) on the main productivity drivers identified by the literature. Panel regressions on a dataset covering up to 125 OECD regions in 17 countries identify the factors associated with high regional productivity, namely rail and road connectivity, knowledge-intensive employment and research and education. Investment in construction and finance is linked to somewhat weaker productivity. Even after taking these factors into account, the Stockholm region benefits from a sizeable productivity advantage, which likely reflects agglomeration effects